Dating Anxiety and Loneliness in Online Dating: The Moderating Effect of Gender - Rinaldi, Martaria Rizky; Azzahra, Octla Fiera Sarah; Hardika, Jelang (Utan Kayu Publishing, 2024)
In the digital age, online dating applications have revolutionized the way young adults form romantic connections, providing both opportunities and challenges. Understanding the psychological impacts of these platforms is crucial. Young adults, while navigating romantic pursuits and various developmental challenges, are susceptible to feelings of loneliness. Dating anxiety is a significant factor that can exacerbate loneliness within this demographic. Moreover, gender differences may influence individuals' experiences in dating situations. This research aims to explore the relationship between dating anxiety and loneliness among users of dating applications and to examine the role of gender as a moderating variable in this relationship. The study employs a quantitative correlational approach, incorporating demographic data and two scales: the Dating Anxiety Scale and the UCLA Loneliness Scale 3. The research participants consist of 250 early adults aged 20-34 who actively use online dating applications. Data analysis involves descriptive analysis and moderation analysis using the Jamovi software. The research findings indicate a significant direct relationship between dating anxiety and loneliness (p less than 0.001). Furthermore, gender was found to have no significant impact on loneliness (p more than 0.05), and the interaction between dating anxiety and gender was not significant (p more than 0.05). This suggests a uniform impact among both genders in the relationship between dating anxiety and loneliness. The study highlights the complex dynamics influencing loneliness among online dating application users. The findings enhance theoretical understanding of how dating anxiety relates to loneliness. Practically, these insights can help developers create features that reduce anxiety and loneliness. Future research should identify other factors influencing these dynamics to further enrich theoretical and practical knowledge in this field.